1985
DOI: 10.1148/radiology.154.3.3918333
|View full text |Cite
|
Sign up to set email alerts
|

Postinflammatory ossicular fixation: CT analysis with surgical correlation.

Abstract: Postinflammatory ossicular fixation is a common problem encountered by the otologic surgeon upon exploration because of conductive hearing loss in patients with chronic otitis media. These nonotosclerotic noncongenital lesions take three pathologic forms: fibrous tissue fixation (chronic adhesive otitis media), hyalinization of collagen (tympanosclerosis), and new bone formation (fibro-osseous sclerosis). Fibrous tissue fixation appears on CT as nonbony, noncalcific soft-tissue debris encasing some or all of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…With spiral CT he detected tympanosclerosis in 10 (3.3%) of 300 patients with chronic otitis media. According to Swartz foci of tympanosclerosis appear as punctate or lattice like masses with calcium density (23). In his study Dr. Eralp could not detect 2 tympanosclerosis cases with CT which were diagnosed clinically and surgically (24).…”
Section: Figure 4 Soft Tissue In Tympanic Cavity Lateral Ssc Defectmentioning
confidence: 98%
“…With spiral CT he detected tympanosclerosis in 10 (3.3%) of 300 patients with chronic otitis media. According to Swartz foci of tympanosclerosis appear as punctate or lattice like masses with calcium density (23). In his study Dr. Eralp could not detect 2 tympanosclerosis cases with CT which were diagnosed clinically and surgically (24).…”
Section: Figure 4 Soft Tissue In Tympanic Cavity Lateral Ssc Defectmentioning
confidence: 98%
“…Post-inflammatory ossicular chain fixation (PIOF) is a common problem in patients with conductive hearing loss [25]. On CT images, three distinctive forms of PIOF can be evaluated:

Presence of fibrous tissue , usually in the niche of oval window, forming a so-called “peristapedial tent” (Fig.

…”
Section: Middle Earmentioning
confidence: 99%
“…In the setting of chronic middle ear inflammation, cholesteatomas arise as the result of tympanic membrane retraction or perforation [24, 25]. …”
Section: Middle Earmentioning
confidence: 99%
“…Clinically, the disease presents in the form of either unilateral or, more rarely, bilateral progressive conductive hearing loss with an intact tympanic membrane [1]. The diagnosis is made at the time of surgery or with the help of preoperative high-resolution CT scans of the temporal bones [4]. Some histopathologic studies [5,6] have been performed to reveal the histologic nature of MHF and confirmed the tympanosclerotic or otosclerotic origin of the fixation.…”
Section: Introductionmentioning
confidence: 99%